Self-Compassion and Eco-Anxiety: Examining Their Relationship in a Greek Sample - Anna Papadimitriou; Eirini Karakasidou (International Journal of Environmental Research and Public Health, 2026)
Background: Eco-anxiety refers to an individual’s emotional response to environmental conditions such as air pollution and climate change. Eco-anxiety has been associated with various psychological variables; however, there is limited research on positive factors such as self-compassion. Previous studies have examined the relationship between eco-anxiety and certain dimensions of self-compassion, such as isolation and mindfulness, but have not investigated its relationship with self-compassion as a whole or with its other dimensions. Methods: The present cross-sectional study aims to address this gap by examining a sample of 586 adults of all genders from different regions of Greece. The participants were collected through convenience sampling and completed two scales: the Self-Compassion Scale and the Hogg Eco-Anxiety Scale (which has undergone a validation process in Greek). Results: Using linear multiple regression analysis, the results showed that isolation has a positive correlation with affective symptoms, rumination and behavioural symptoms. Mindfulness has a negative correlation with affective symptoms, behavioural symptoms and anxiety about personal impact. Anxiety about personal impact is positively associated with self-kindness and over-identification. Conclusions: Instead of assuming a uniform relationship between self-compassion and eco-anxiety, this dimensional approach may help clarify whether specific self-compassion processes are more relevant to particular emotional, cognitive, and behavioural manifestations of eco-anxiety.